2004
DOI: 10.1002/cncr.20227
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose thiotepa and etoposide in children with poor‐prognosis brain tumors

Abstract: BACKGROUNDOutcome data were analyzed for 27 patients who were affected with recurrent or newly diagnosed high‐risk brain tumors and who underwent high‐dose chemotherapy with triethylenethiophosphoramide (thiotepa) and etoposide in addition to autologous stem cell transplantation between May 1992 and September 2002.METHODSFifteen males and 12 females (median age, 11 years) were included in the study. Twelve patients had newly diagnosed high‐risk brain tumors, and 15 patients had recurrent brain tumors. The cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…But pediatric conditioning regimens containing thiotepa were not reported to have an exceedingly high incidence of VOD. [30][31][32][33] Most recently a treatment regimen consisting of cyclophosphamide, thiotepa and carboplatin was assessed for the occurrence of VOD in adults. The calculated plasma concentration-time curves (AUCs) for cyclophosphamide and its activated metabolites showed that the incidence of VOD was rather linked to bioactivated cyclophosphamide than to the administration of thiotepa.…”
Section: Discussionmentioning
confidence: 99%
“…But pediatric conditioning regimens containing thiotepa were not reported to have an exceedingly high incidence of VOD. [30][31][32][33] Most recently a treatment regimen consisting of cyclophosphamide, thiotepa and carboplatin was assessed for the occurrence of VOD in adults. The calculated plasma concentration-time curves (AUCs) for cyclophosphamide and its activated metabolites showed that the incidence of VOD was rather linked to bioactivated cyclophosphamide than to the administration of thiotepa.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal administration has resulted in myelopathy [28]. Most recent studies do not report any significant neurologic toxicities associated with treatment [29][30][31][32][33].…”
Section: Thiotepamentioning
confidence: 97%
“…The survival rate was reported as a broad range, 5-54%, by studies done in various different situations with regard to pre-transplant conventional chemotherapy, conditioning regimens, disease status prior to HDCT, and adjuvant therapy. Some studies did not separate recurrent medulloblastoma from high-risk medulloblastoma or other brain tumors types in their study group (8, 12). Grururangan et al (13) reported a 3-yr overall survival rate of 14% in recurrent medulloblastoma patients who underwent HDCT/ASCT and received no irradiation before relapse, while no survival was found in those who underwent HDCT/ASCT receiving irradiation before relapse and in those who did not undergo HDCT/ASCT and received only standard SC.…”
Section: Discussionmentioning
confidence: 99%
“…Fagioli et al (12) reported that patients with CR status following a poor prognosis brain tumor had a survival rate of 50.6% compare to 19.6% for those without CR status. Cheuk et al (14) reported that long-term survival in CR patients before HDCT was 63% (5 out of 8 CR patients survived), but that 5 PR patients all died in the study of single transplantation in high-risk or recurrent CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation